On the effects of L2 perception and of individual differences in L1 production on L2 pronunciation - Kartushina, Natalia; Frauenfelder, Ulrich H. (Frontiers in Psychology, 2014)
The speech of late second language (L2) learners is generally marked by an accent. The dominant theoretical perspective attributes accents to deficient L2 perception arising from a transfer of L1 phonology, which is thought to influence L2 perception and production. In this study we evaluate the explanatory role of L2 perception in L2 production and explore alternative explanations arising from the L1 phonological system, such as for example, the role of L1 production. Specifically we examine the role of an individual’s L1 productions in the production of L2 vowel contrasts. Fourteen Spanish adolescents studying French at school were assessed on their perception and production of the mid-close/mid-open contrasts, /ø-œ/ and /e-ε/, which are, respectively, acoustically distinct from Spanish sounds, or similar to them. The participants’ native productions were explored to assess (1) the variability in the production of native vowels (i.e., the compactness of vowel categories in F1/F2 acoustic space), and (2) the position of the vowels in the acoustic space. The results revealed that although poorly perceived contrasts were generally produced poorly, there was no correlation between individual performance in perception and production, and no effect of L2 perception on L2 production in mixed-effects regression analyses. This result is consistent with a growing body of psycholinguistic and neuroimaging research that suggest partial dissociations between L2 perception and production. In contrast, individual differences in the compactness and position of native vowels predicted L2 production accuracy. These results point to existence of surface transfer of individual L1 phonetic realizations to L2 space and demonstrate that pre-existing features of the native space in production partly determine how new sounds can be accommodated in that space.